The Effect of Blended Learning and Teacher-Student Interaction on the Learning Motivation of SMAN 1 Depok City Students - Sari, Rini Yunita; Hermawan, Husnita (International Journal of Educational Technology and Learning, 2022)
The purpose of this study is to determine the influence of blended learning and teacher-student interaction on student learning motivation at senior high school 1 Depok City. This research uses quantitative methods with the paradigm of positivism. The data collection technique was through the distribution of questionnaires with a total population of 600 students and a sample of 263 students in class X and XI of senior high school 1 Depok City. The results of the influence of blended learning on student learning motivation are categorized in terms of online content indicators, live events and collaboration. The results of the study on the effect of teacher-student interaction on student learning motivation well categorized in terms of indicators of openness, empathy, support, a sense of positivity and equality. The results of analysis and hypothesis testing show that blended learning and teacher-student interaction have a positive and significant effect on the learning motivation of students of senior high school 1 Depok City. From the results, the research can influence blended learning and teacher-student interaction on the learning motivation of students of senior high school 1 Depok City by 27.5% and the remaining 72.5% is influenced by other factors, namely factors of the students themselves, adequate facilities and infrastructure, family environment, school and social. It is recommended that in blended learning teachers are required to be more creative, innovative and communicative when delivering material, and the interaction between teachers and students is further improved in order to generate student learning motivation.